Simulation and compensation of thermal lensing in optical systems - Rall, Phillip Lino; Förster, Daniel; Graf, Thomas; Pflaum, Christoph (Optics Express, 2022)
High-power optical systems are used in a number of industrial applications. One difficulty in designing such systems is that the beam itself is a significant source of heat, which changes the optical properties of the system. To reduce this effect, we propose a new thermal lensing compensation technique based on a detailed analysis of the optical properties of the high-power optical system. To this end, we have developed a new ray tracing simulation technique that accurately models optical propagation through inhomogeneous, anisotropic, and deformed media. This model enables the performance of systems in physically realistic situations to be evaluated efficiently. Experimental comparisons were conducted to validate the simulation. We found excellent agreement between the simulation and the measured data. We have validated the simulation technique for a single lens setup and a complex optical scanner system.
CRIS-Team Scopus Importer:2022-10-21